The reliability of an inline hockey agility test - Redman, C.; Cronin, J. (Journal of Human Movement Studies, 2005)
The purpose of this study was to develop an easily administered inline hockey agility test specific to the movement patterns of players using skates and thereafter establish the reliability of this protocol. Ten competitive male inline hockey players of national and regional representative level, were tested on two occasions. The tests involved timing forward and backward skating (15m and 30m) and the new inline agility test. Reliability was established using co-efficients of variation and intraclass correlation co-efficients (ICC).Within trial variation for the agility test was less than 3% for both testing occasions (CV=1.9% and 2.7%). Test-retest reliability was practically perfect (ICC=0.95). The inline agility test was very highly related to both forward skating 15 and 30m times (r=0.84 to 0.89) but was not significantly related to the backward skating 15 and 30m times (r=0.48). It would seem that the ability to skate forward explains a great deal of the shared variance (~70 to 80%) of the new agility test, even though a large component of the agility test (29%) involved backward skating.